Tourism Development of Sakura Village in Sidomulyo Village through Community Based Tourism Approach - Abigail Farhan Damiri; Ach. Apriyanto Romadhon (IRDH International Journal of Social Sciences & Humanities, 2025)
This study aims to determine how the application of the concept of Community Based Tourism in the process of developing sakura village tourism. Second, this research aims to determine the impact of the development of cherry blossom village tourism based on Community Based Tourism. The background of this research is the development of sakura village tourism which departs from the response to the program from the Batu City Tourism Office so that the RT 05 RW 11 community initiates to build new alternative tourism. The research method used is a qualitative method with a descriptive approach. The data collection technique used is the field observation method, interviews with the management of the sakura village and Sidomulyo Village government officials, and documentation to obtain concrete evidence in the form of photos and documents. The results of the research are the process of developing community-based tourism or Community Based Tourism (CBT). The application of the CBT concept in the development of sakura village tourism can be seen through community participation from development to the establishment of tourism organizations, funding sources that come from community self-help, community empowerment in tourism development. As well as the impact of CBT-based sakura village tourism development, namely increasing community enthusiasm through various activities, creating a clean and sustainable environment, opening productive economic opportunities for the community and as a new cultural learning phenomenon for the surrounding community.